The Plan for Energy Saving and Efficiency as an Example of the University of Valladolid's Commitment to Sustainability - Eduardo Garcia-Ochoa; Helena Villarejo-Galende; Sergio Lorenzo Gonzalez-Gonzalez (Universitas Diponegoro, 2023)
This paper presents the University of Valladolid's Plan for Energy Saving and Efficiency (February 2023) and focuses on the keys developed in relation to the sustainable design and use of university buildings and the promotion of sustainable mobility, as well as on the objectives pursued by the Plan: to reduce the environmental impact and the associated energy costs, eliminate fossil fuels and seek self-consumption. The University of Valladolid has been working for years to improve its energy and environmental performance, using biomass as the main energy resource for heating and sanitary hot water systems in most of its facilities, for the construction of sustainable and efficient buildings, for carrying out energy renovations and continuous actions to improve energy efficiency in existing buildings, and for promoting sustainable mobility models among the university community. With these actions, the University of Valladolid has managed to reduce emissions of thousands of tons of CO2 into the atmosphere each year, improving conditions in university spaces and keeping energy consumption stable. This reduction in energy consumption has made it possible to contain energy costs in global scenarios of rising prices, as well as to minimize the application of harsh measures to reduce energy consumption (closing buildings, turning off air conditioning, etc.) that most higher education institutions in our country have been forced to apply.